Vida hifenizada: traduzibilidade como exercício de individuação - Kraus, Damian José (2008)
This thesis intends to outline a problem of translatability as an exercise of individuation based on the concept found in the works by Deleuze & Guattari, particularly, the book Mille Plateaux. This translatability is pragmatically located in the in-between of the Spanish and Portuguese languages a tension of siamese tongues. This work is composed, first of all, of a thematic Introduction, with the addition of a preliminary approach in the manner of short Essays. Subsequently, it unfolds through three blocks: the first block highlights the intensification of this convergence of sister languages, from where the denominated pure language emerges. The second block is an exercise of investigative intervention in this convergence, which is proposed as exercise of individuation. The third block is geared to the intensity that comes from such exercise, as a procedure of nomadic thought. It is important to mention that this thesis will be linked to the notion of state of translation, elaborated by the author in his master s thesis, which has provided theoretical and methodological elements for the development of this work